Micronests in Tumor Stroma is a Prognostic Classifier in Nasopharyngeal Carcinoma - Almangush, Alhadi; Ruuskanen, Miia; Hagström, Jaana; Kosma, Veli-Matti; Mäkitie, Antti A.; Leivo, Ilmo (Ovid Technologies (Wolters Kluwer Health), 2026)
The assessment of micronests in tumor stroma has been introduced recently for the prognostication of human malignancies. In this multicenter study, we included a total of 110 patients treated for nasopharyngeal carcinoma (NPC) at one of the Finnish University Hospitals. All available hematoxylin and eosin (H&E)-stained slides were scanned. Assessment of micronests in tumor stroma was conducted on scanned HE-stained slides. Presence of micronests in tumor stroma had a significant prognostic value in predicting overall survival in the multivariable analysis with a hazard ratio (HR) of 1.92 (95% CI: 1.14-3.24, P=0.01). Similarly, in the multivariable analysis of disease-specific survival, micronests in tumor stroma had a significant prognostic value with an HR of 1.87 (95% CI: 1.00-3.48, P=0.04). In addition, the presence of micronests in tumor stroma showed a significant association with keratinizing and EBV-negative tumors (P<0.001). In conclusion, the evaluation of micronests in tumor stroma can be used as a prognostic classifier in NPC and they can be assessed in routine H&E-stained sections.